Probing plasmonic excitation mechanisms and far-field radiation of single-crystalline gold tapers with electrons. (11th December 2020) - Lingstädt, Robin; Talebi, Nahid; Guo, Surong; Sigle, Wilfried; Campos, Alfredo; Kociak, Mathieu; Esmann, Martin; Becker, Simon F.; Okunishi, Eiji; Mukai, Masaki; Lienau, Christoph; van Aken, Peter A.
Abstract : Conical metallic tapers represent an intriguing subclass of metallic nanostructures, as their plasmonic properties show interesting characteristics in strong correlation to their geometrical properties. This is important for possible applications such as in the field of scanning optical microscopy, as favourable plasmonic resonance behaviour can be tailored by optimizing structural parameters like surface roughness or opening angle. Here, we review our recent studies, where single-crystalline gold tapers were investigated experimentally by means of electron energy-loss and cathodoluminescence spectroscopy techniques inside electron microscopes, supported by theoretical finite-difference time-domain calculations. Through the study of tapers with various opening angles, the underlying resonance mechanisms are discussed. This article is part of a discussion meeting issue 'Dynamic in situ microscopy relating structure and function'.